A multicenter phase 2 single arm study of cabozantinib in patients with advanced or unresectable renal cell carcinoma pre-treated with one immune-checkpoint inhibitor: The BREAKPOINT trial (Meet-Uro trial 03). Issue 1 (February 2023) - Procopio, Giuseppe; Claps, Mélanie; Pircher, Chiara; Porcu, Luca; Sepe, Pierangela; Guadalupi, Valentina; De Giorgi, Ugo; Bimbatti, Davide; Nolè, Franco; Carrozza, Francesco; Buti, Sebastiano; Iacovelli, Roberto; et al.
Background: First-line therapies based on immune-checkpoint inhibitors (ICIs) significantly improved survival of metastatic renal cell carcinoma (mRCC) patients. Cabozantinib was shown to target kinases involved in immune-escape and to prolong survival in patients pre-treated with tyrosine-kinase-inhibitors (TKIs). The impact of ICIs combinations in first line on subsequent therapies is still unclear. Methods: This is an open label, multicenter, single arm, phase II study designed to assess activity, safety and efficacy of cabozantinib in mRCC patients progressed after an adjuvant or first line anti-Programmed Death (PD)-1/PD-Ligand (PD-L) 1-based therapy. Primary endpoint was progression free survival (PFS), secondary endpoints were overall survival (OS), objective response rate (ORR) and safety. Results: 31 patients were included in the analysis. After a median (m) follow-up of 11.9 months, mPFS was 8.3 months (90%CI 3.9-17.4) and mOS was 13.8 months (95%CI 7.7-29.0). ORR was 37.9% with an additional 13 patients achieving disease stability. Grade 3-4 adverse events occurred in 47% of patients, including more frequently creatine phosphokinase (CPK) serum level elevation, neutropenia, hyponatremia, diarrhea, hand-food syndrome, oral mucositis and hypertension. Conclusions: The BREAKPOINT trial met its primary endpoint showing that cabozantinib as second line therapy after ICIs was active in mRCC. Safety profile was manageable. Trial registration number: NCT03463681 - A Study of CaBozantinib in Patients With Advanced or Unresectable Renal cEll cArcinoma (BREAKPOINT) -https://clinicaltrials.gov/ct2/show/NCT03463681